44th AIAA Aerospace Sciences Meeting and Exhibit 2006
DOI: 10.2514/6.2006-206
|View full text |Cite
|
Sign up to set email alerts
|

The Ice Particle Threat to Engines in Flight

Abstract: This paper discusses jet engine powerloss and damage due to ingestion of ice particles. In the mid-90s several commercial airplane jet engines experienced more frequent powerloss in ice particle conditions, resulting in a focused investigation, and a greater awareness that led to recognition of similar events on other aircraft. Since the mid-90s, events have been more numerous, and costly, and have generated greater industry interest. These events have been predominately associated with flight at high altitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
159
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(176 citation statements)
references
References 19 publications
(26 reference statements)
4
159
0
1
Order By: Relevance
“…First HIWC studies (Mason et al, 2006) indicated that this new form of icing (now referred to as ice crystal icing) was due to the production of high concentrations of small ice crystals by deep convection. In this context 23 flights were performed over the Darwin area, mainly over the ocean north of Australia, during the monsoon season.…”
Section: Data Processingmentioning
confidence: 99%
“…First HIWC studies (Mason et al, 2006) indicated that this new form of icing (now referred to as ice crystal icing) was due to the production of high concentrations of small ice crystals by deep convection. In this context 23 flights were performed over the Darwin area, mainly over the ocean north of Australia, during the monsoon season.…”
Section: Data Processingmentioning
confidence: 99%
“…The events reported engine damage due to shed ice or loss of engine power caused by flameout, surge or rollback due to a lower airflow into the combustion chamber in combination with ice ingestion. Mason et al [95] concluded that the engine rollbacks were caused by build up of ice between the blades of the low-pressure compressor in the engine core, see Figure 1.5. The engines could be restarted and regain normal operation when the aeroplane descended to an altitude with warmer air.…”
Section: Ice Crystal Icingmentioning
confidence: 99%
“…An analysis by Mason et al [95] of the events of loss of power of jet engines reported since 1990 implied a connection with atmospheric ice crystals that were encountered in convective clouds. The resulting database [13,95] it has been concluded that approximately 90% of the events occurs in (sub-)tropical regions between 38…”
Section: Ice Crystal Icingmentioning
confidence: 99%
See 1 more Smart Citation
“…original hypotheses of Mason et al, (2006) was obtained in an exploratory in-situ flight campaign in HIWC conditions (Grandin et al, 2014). In more recent years, icing of aircraft air data probes (e.g.…”
mentioning
confidence: 99%